Determination of total factor productivity in Italian regions - Guido Ascari; Valeria Di Cosmo (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2004)
This paper investigates the determinants of TFP for Italian regions. We find strong evidence in favour of the factors commonly suggested by the theoretical literature. In particular, R&D expenditures and the number of researchers are positively related to regional TFP. Moreover, human capital is an important determinant of TFP. Finally, we find a strong difference between Northern and Southern regions, particularly regarding the effect of research activity and social capital. Our results are robust across different estimation methods.
Keywords: O47; C23; R11; 330; Total factor productivity; Italian regions; panel data; Produktivität; Regionale Disparität; Italien